Relationship between Serum Vitamin D Levels and Asthma Control in Adult Patients - Sabaruddin, Haeriah; Djamaluddin, Fauzan; Ilyas, Muh.; Iskandar, Harun; Lihawa, Nurjannah; Nurisyah, Siti; Wiriansya , Edward Pandu (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Asthma is a heterogeneous disease characterized by respiratory symptoms that vary both over time and in intensity, along with limited expiratory airflow. This heterogeneity is related to the patient's genetic and environmental phenotype. Vitamin D levels can affect the severity of asthma and the success of asthma treatment. Vitamin D can also influence the effectiveness of glucocorticoid therapy as an anti-inflammatory. This study aimed to determine the relationship between serum vitamin D levels and asthma control, severity, obstruction, and exacerbation levels. This research was a descriptive cross-sectional study on asthma patients at Wahidin Sudirohusodo Hospital and its network for the period October–December 2023. Each research subject had a venous blood sample taken and then checked vitamin D levels at the Hasanuddin University Teaching Hospital Research Laboratory. This research involved 72 research subjects. Most of the research subjects were female (61.1%), aged <45 years (52.8%), worked as housewives (29.2%), had overweight BMI (33.3%), and had a history of atopy (59.7%). The degree of airway obstruction in the study subjects was mostly mild (66.7%) and the degree of severity was intermittent, persistent, and the degree of exacerbation in the same sample (33.3%). The results of the study showed a relationship between vitamin D levels and nutritional status, history of atopy, degree of asthma control using the ACT questionnaire, degree of stable asthma, and exacerbations where p<0.05. Also, it is found that a weakly positive connection (R: 0.2–0.4) between vitamin D levels and ACT, FEV1, FEV/FVC. There is a relationship between vitamin D levels and nutritional status, history of atopy, degree of asthma control using the ACT questionnaire, degree of stable asthma, and exacerbations. There was a relationship between vitamin D levels and the degree of obstruction assessed by spirometry in this study.